Tendensi dalam Pemberitaan CNN Tentang Penggunaan Ban Lengan One Love pada FIFA World Cup Qatar 2022 - Kenny Andika; Eqi Safitri (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2023)
Essential news in the media about FIFA’s decision not to use the One Love armband during the FIFA world Cup Qatar 2022 on CNN arabic news and uses the critical discourse analysis version of Teun A.van Dijk in three structure: micro-structure, superstructure and macro-structure. This research is a descriptive qualitative research and the formulation of the problem in this research how the tendency in reporting on the use of the One Love armband at FIFA World Cup Qatar 2022. The results showed that, CNN in coveying news that was far intriguing and sharp and the news presented like neutral, it’s just that after looking at the tendency approach with van Dijk’s critical discourse analysis theory it was found that there was a media tendency in supportting to use the One Love armband which symbolizes for support the LGBT community (lesbian, gay, bisexual and transgender) in green field.